Challenges and Opportunities in the Supply of Living Kidney Donation in the UK National Health Service: An Economic Perspective. Issue 11 (27th May 2022) - Morris, Tiyi; Maple, Hannah; Norton, Sam; Chilcot, Joseph; Burnapp, Lisa; Draper, Heather; Mamode, Nizam; McCrone, Paul
Abstract : End-stage kidney disease is a significant burden on the healthcare systems of many countries, and this is likely to continue because of an increasingly aging and comorbid population. Multiple studies have demonstrated a significant clinical benefit in transplantation when compared with dialysis, however, there continues to be a shortage of donor kidneys available. This article provides an economic perspective on issues pertinent to living kidney donation and transplantation. Although ethics, equity, and cultural considerations often seem at odds with economic concepts around resource allocation, this article explains the situation around supply and demand for living kidneys and illustrates how this has been addressed in the economic literature. The article discusses different policy recommendations for resolving the imbalance between supply and demand in kidney donation, through policies under 3 main approaches: increasing supply, decreasing demand, and improving the allocation of kidney supply.